(untitled) (Web of Teachers: Inderscience Research, 2024)
The globalization of the world leads to the deformation of these religions, the real reason for this is the situation in the world and the gradual decrease in tolerance of people. Through our articles like this, we try to instill in people the ideas of tolerance in religions.